2010
DOI: 10.1086/653940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clinical and Virological Parameters on the Level of Neutralizing Antibody against Pandemic Influenza A Virus H1N1 2009

Abstract: About 10% of these convalescent patients do not have a seroprotective NAT and may benefit from vaccination to prevent reinfection. The convalescent NAT correlated well with the initial viral load and was independently associated with severity of the viral illness, including pneumonia. The findings provide both the clinical and virological markers for identifying potential convalescent plasma donors with high serum NAT, which can be used to produce hyperimmune intravenous immunoglobulin in a randomized treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 20 publications
8
60
1
1
Order By: Relevance
“…had the highest geometric mean titers, suggesting that this remains the optimal time frame for the collection of convalescent-phase sera. These results are consistent with those of Miller et al (20) and Hung et al (15), who reported that 11% of confirmed 2009 H1N1 cases in England failed to develop HI antibody titers of Ն32 and 10% of confirmed cases in Hong Kong failed to develop neutralizing antibody titers of Ն40. Similar to our results, Hung et al (15) also found that the MN assay detected a higher seroconversion rate (89%) than the HI assay (82%).…”
Section: Discussionsupporting
confidence: 92%
“…had the highest geometric mean titers, suggesting that this remains the optimal time frame for the collection of convalescent-phase sera. These results are consistent with those of Miller et al (20) and Hung et al (15), who reported that 11% of confirmed 2009 H1N1 cases in England failed to develop HI antibody titers of Ն32 and 10% of confirmed cases in Hong Kong failed to develop neutralizing antibody titers of Ն40. Similar to our results, Hung et al (15) also found that the MN assay detected a higher seroconversion rate (89%) than the HI assay (82%).…”
Section: Discussionsupporting
confidence: 92%
“…Patients with natural infection were randomly selected from those who suffered from pandemic H1N1 2009 influenza virus infection confirmed by either reverse transcriptase PCR or viral culture and donated their convalescent plasma for the treatment of patients with severe pandemic influenza (18,19,49). The vaccine recipients received a monovalent, split-virus, inactivated, nonadjuvanted vaccine containing 15 g of hemagglutinin of influenza A/California/07/2009 (H1N1) virus (Panenza; Sanofi Pasteur, France).…”
Section: Participantsmentioning
confidence: 99%
“…The CMN assay for the pandemic H1N1 A/HK/415742/2009 was carried out in microtiter plates with neutralization of the virus cytopathic effect as the endpoint in Madin-Darby canine kidney (MDCK) cells according to a previously described method (19). Briefly, serial serum dilutions in duplicate started from 1:10 were mixed with 100 50% tissue culture infective doses for 2 h at 37°C and added to MDCK cells.…”
Section: Participantsmentioning
confidence: 99%
“…There is evidence that A(H1N1)pdm09 virus induces a weak host immune response [16,17], which could explain the low antibody titres. Hung et al reported a similar percentage of seronegative patients, when they found that 10% of confirmed patients did not generate antibody responses to the pandemic virus [15]. Our data indicate that the presence of high titres of antibodies to the non-pandemic strains A/swine/Iowa/00239/2004(H1N1) and A/swine/Texas/4199-2/98(H3N2) did not generate protection to the A(H1N1)pdm09 virus infection, since hospitalised patients with confirmed pandemic influenza had protective antibody titres to these swine viruses.…”
Section: Discussionmentioning
confidence: 89%
“…The overall seroprevalence for A/Mexico/4482/2009(H1N1) pandemic virus was 45%, indicating that 55% of this exposed population remained without immunity to the pandemic virus. Even in the confirmed case group, the GMT was relatively low (25) and is not considered protective [14,15]. There is evidence that A(H1N1)pdm09 virus induces a weak host immune response [16,17], which could explain the low antibody titres.…”
Section: Discussionmentioning
confidence: 99%